Fuel Properties of Croton megalocarpus, Calophyllum inophyllum, and Cocos nucifera (coconut) Methyl Esters and their Performance in a Multicylinder Diesel Engine - Atabani A.E.; Badruddin I.A.; Mahlia T.M.I.; Masjuki H.H.; Mofijur M.; Lee K.T.; Chong W.T. (Wiley-VCH Verlag, 2023)
Biodiesel has been considered recently as a viable alternative to fossil diesel fuels. This study aims to evaluate the potential of biodiesel production from Croton megalocarpus oil and compared it with coconut (Cocos nucifera) and Calophyllum inophyllum methyl esters. The study presents the physical and chemical properties of Croton megalocarpus, Calophyllum inophyllum and coconut methyl esters (CMME, CIME, and COME) together with their 10 and 20 % blends by volume (B10 and B20). This is followed by evaluating their blends in a multicylinder Mitsubishi Pajero diesel engine. It has been found that the properties of all biodiesel and their blends are comparable with ASTM D6751 and ASTM D7467 standards, respectively. Over the entire range of speed, it was found that the B10 and B20 blends of CMME, CIME, and COME result in average reduction in torque and brake power (BP) along with increased brake-specific fuel consumption (BSFC) compared to pure diesel fuel. With respect to engine emissions, the fuel blends resulted in an average reduction in carbon monoxide (CO) and hydrocarbon (HC) emissions. However, the CMME and COME blends resulted in increased emissions of nitrogen oxides (NO) whereas CIME emits lower NO compared to pure diesel. It is concluded that B10 and B20 biodiesel blends can be used as diesel fuel substitutes without additional modifications. Copyright 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim